Using fractal dimensions for characterizing intra-urban diversity. The example of Brussels - Isabelle Thomas; Marie-Laurence De Keersmaecker; Pierre Frankhauser (European Regional Science Association (ERSA), 2003)
The objective of this paper is to compare fractal-based parameters calculated by different fractal methods for urban built-up areas, and to link the observed spatial variations to variables commonly used in urban geography, urban economics or land use planning. Computations are performed on Brussels. Two fractal methods (correlation and dilation) are systematically applied for evaluating the fractal dimension of built-up surfaces; correlation is used to evaluate the fractal dimension of the borders (lines). Analyses show that while fractal dimension is ideal for distinguishing the morphology of Brussels, each estimation technique leads to slightly different results. Interesting associations are to be found between the fractal dimensions and rent, distance, income and planning rules. Despite its limitations, fractal analysis seems to be a promising tool for describing the morphology of the city and for simulating its genesis and planning. The model is robust: it replicates the urban spatial regularities and patterns, and could hence fruitfully be integrated into intra urban simulation processes.
Keywords: 330